Efek dari Latihan Ketahanan Aerobik vs HIIT terhadap asupan energi, asupan zat gizi makro, dan tingkat VO2Max pada Peserta Pusat Kebugaran - Kuswari, Mury; Gifari, Nazhif; Himarwan, Aditya (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2021)
The purpose of the study Nowadays, there are many people who participate in fitness centre to maintain their health and fitness. There are many ways to increase VO2Max, an indicator of cardiorespiratory fitness, two of many were High-Intensity Interval Training (HIIT) and traditional aerobic endurance training. In other hand exercise in any type of way required extra energy, resulting in increased energy and macronutrient intake. Was to analyse the effects of HIIT vs. Aerobic Endurance Exercise on energy intake, macronutrient intake, and VO2Max of fitness centre participants in Depok.. Materials and methods 26 participants were recruited voluntarily from one of fitness centre in Depok, West Java, Indonesia, then randomized into HIIT Intervention Group and aerobic endurance exercise intervention group for 3 months. Energy and macronutrient intake were assessed before and after intervention. Bleep test was done to determine VO2Max Level before and after intervention. Results. Paired t-test between before and after intervention showed that there’s significant difference (p<0.05) on VO2Max, while independent sample t-test showed that there’s no significant difference between both type of exercise. Conclusions. This study shows that there was no effect of both HIIT and Aerobic Endurance Training on energy and macronutrient intake. However, both interventions increase VO2Max as an indicator of fitness level. Shorter time for HIIT may be useful for increasing VO2Max level on busy individual.